PEMBERDAYAAN KADER POSYANDU LANSIA TENTANG SENAM KAKI DIABETES MELLITUS DI WILAYAH KERJA PKM KAYON KOTA PALANGKA RAYA - Berthiana T; Meity K. Mewo (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
An elderly person who is over 60 years old. The most common problem faced by the elderly is health problems, one of which is diabetes mellitus. Diabetes mellitus is a group of metabolic diseases characterized by high levels of glucose in the blood. The most common complications experienced by diabetic mellitus are complications in the legs that result in foot sores (diabetic ulcers). These complications are prevented by doing diabetic foot gymnastics regularly to facilitate blood circulation.The results of community service conducted showed an increase in the knowledge of participants (elderly posyandu cadres) based on the results of pre tests and post tests after the empowerment of diabetic mellitus foot gymnastics. Of the number of participants (16 people) after the question and answer lecture and demonstration and re-demonstration was on the results of the highest score of 8 pre-tests as many as 2 people and the highest post test results of 9 as many as 3 people, based on these results participants understood the importance of doing diabetic mellitus foot gymnastics.